Efficacy and safety of probiotics in the treatment of Candida‐associated stomatitis. Issue 3 (19th August 2013) - Li, Duo; Li, Qingfu; Liu, Chuanxia; Lin, Mei; Li, Xiaoying; Xiao, Xiaoying; Zhu, Zhu; Gong, Qimei; Zhou, Hongmei
Summary This study aimed at evaluating the short‐term efficacy and safety of probiotics as an aid in the treatment of Candida‐associated stomatitis in a randomised controlled trial. A total of 65 patients were randomly assigned to receive oral local antifungal agents alone (gargle 2% sodium bicarbonate solution for 30 s, wait 10 min and then apply 2% nystatin paste) or these agents plus local probiotics (the mixture of Bifidobacterium longum, Lactobacillus bulgaricus and Streptococcus thermophilus) three times per day for 4 weeks. Parameters related to hyperaemia, visual analogue scale scores, culture of resting saliva and a lingual dorsum swab and adverse reactions were assessed or recorded in the beginning, middle and end of treatment. Although the baseline characteristics of the participants were similar, both groups showed a significant reduction in pain level and hyperaemia on the tongue mucosa (P = 0.000) after 4‐week application. However, despite the reduction in hyperaemia in the probiotic group, these improvements did not display statistically significant differences. The detection rate of Candida spp. was 100% before treatment and 8.21% in the experimental group and 34.6% in the control group after treatment. The detection rate of Candida spp. decreased (P = 0.000) in both groups and was significantly lower in the probiotic group than the control group (P = 0.038). Other analysed micro‐organisms, including the decreased detection rate for Lactobacillus spp. (P = 0.049) and the increased detection rate for Staphylococcus epidermidis (P = 0.019), did not display consistent change trends in the probiotics group. Compared with conventional antifungal therapies for oral candidiasis, the inclusion of locally administered probiotics helped improve certain clinical conditions and reduced the prevalence of Candida spp., although the impact of probiotics on oral bacterial species remains to be further studied.